EDUKASI DAN PENYULUHAN K3 FISIOTERAPI UNTUK MENINGKATKAN PENGETAHUAN DAN PENCEGAHAN LOW BACK PAIN DI PT. NIAGAMAS GEMILANG - Wanda Sepviani Putri; Anita Faradilla Rahim; Muammar Rizanzani (Health Care : Journal of Community Service, 2025)
Introduction: Working in a position of carrying heavy objects for long periods, as experienced by palm oil plantation workers, can cause musculoskeletal disorders (MSDs). MSDs arise from non-ergonomic working postures, long working durations, and monotonous movements, which ultimately have a negative impact on productivity and health. Objective: To educate about low back pain, especially about the symptoms and causes, and to conduct independent exercises at home to prevent low back pain for PT. Niagamas Gemilang workers. Method: This counseling is in the form of health promotion about low back pain, using posters as media, with the aim of public understanding about low back pain, conducting questions and answers to find out information about complaints experienced by the community, and educating with exercises and treatments that can be done independently. Conclusion: The counseling process went well, the workers were able to follow and understand the exercises that had been taught, this activity obtained results in the form of understanding related to the exercises that had been taught from 0% to 100% after the counseling was carried out so that it could help workers prevent low back pain.